DETERMINANTS OF WORKING CAPITAL IN INDIAN REALTY SECTOR - Shivakumar; Thimmaiah, Babitha (International Journal of Research -GRANTHAALAYAH, 2021)
Working capital is important aspect which ensures sufficient short-term capital to maintain the firm’s day-to-day operations and creating maximum value to the firm. As working capital may have a major impact on profitability, understanding the firm-specific determinants of working capital is important. This study was conducted on the firm-specific determinants of working capital in the Indian Realty Sector. The independent variables employed in the study includes firm size, asset tangibility, leverage, profitability, sales growth, and fixed assets growth, while the dependent variables employed in the study are inventory, receivables, payables, and cash conversation days. The study based on the sample of thirteen companies of Indian Realty Sector, of which five were large-cap, five were mid-cap, and three are small-cap companies. The study was conducted for the period of 2011-20. The study employed fixed-effects panel regression to analyse the significance of the firm-specific determinants of working capital in the Indian Realty Sector.